2002
DOI: 10.1016/s1359-6454(02)00272-0
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermal stability of Nd–Fe–Co–Al bulk metallic glass

Abstract: The thermal stability of Nd 60 Fe 20 Co 10 Al 10 bulk metallic glass (BMG) has been studied by differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), isochronal dilatation and compression tests. The results show that the glass transition of the BMG takes place quite gradually between about 460 and 650 K at a heating rate of 0.17 K/s. Several transformation processes are observed during continuous heating with the first crystallization process beginning at about 460 K, while massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 43 publications
(87 reference statements)
0
35
0
Order By: Relevance
“…Ingots of Nd 60 Al 10 Ni 10 Cu 202x Fe x (x ¼ 0; 5,7,10,15,20) were prepared by arc-melting a mixture of the pure elements Nd, Al, Ni, Cu and Fe with a purity of at least 99.9% in titanium-gettered argon atmosphere. Cylindrical specimens of 3 mm in diameter and 70 mm in length were prepared from the pre-alloyed ingots by suction casting into a copper mold.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingots of Nd 60 Al 10 Ni 10 Cu 202x Fe x (x ¼ 0; 5,7,10,15,20) were prepared by arc-melting a mixture of the pure elements Nd, Al, Ni, Cu and Fe with a purity of at least 99.9% in titanium-gettered argon atmosphere. Cylindrical specimens of 3 mm in diameter and 70 mm in length were prepared from the pre-alloyed ingots by suction casting into a copper mold.…”
Section: Methodsmentioning
confidence: 99%
“…Serrated flow phenomenon during nanoindentation was already found at low strain rates [7 -10]. In this work, the plastic deformation in Nd 60 Al 10 Ni 10 Cu 202x Fe x (x ¼ 0; 5,7,10,15,20) was studied by using nanoindentation experiments and atomic force microscopy. The effect of the microstructure on the serrated flow behavior is studied in this alloy system.…”
Section: Introductionmentioning
confidence: 95%
“…These behaviors, the endothermic peak in the immediate aftermath of the exothermic peak, agree well with previously published results on Nd-based amorphous alloys. 9) In these published results, the broad exothermic peak was attributed to an early crystallization or growth of crystalline phases. In this study, in order to elucidate the broad exothermic peak, the DTA measurement was carried out repeatedly.…”
Section: Methodsmentioning
confidence: 92%
“…Also, the crystallization temperatures of samples by the gas jet flow type electromagnetic levitation process differ slightly from those of the as-cast bulk metallic glass (BMG) and the melt-spun ribbon in the published results. 9) One reason is that the method of preparation and the cooling condition of samples by the containerless process differ from those of the as-cast BMG and the melt-spun ribbon in B. C. Wei et al…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that many metallic glasses do not actually exhibit Newtonian behavior in the supercooled liquid region, and in particular this is true at high strain rates. Kawamura et al [22] and Wei et al [23] showed that the plastic behavior was strongly dependent on the strain rate. The Newtonian behavior of Nd 60 Fe 20 Co 10 Al 10 bulk metallic glass changed to non-Newtonian behavior when the strain rate was increased from 1.4!10 K4 to 1.4!10 K2 s K1 at 503 K. However, the effects of strain rate in BMGs are dependent on the loading conditions and chemical components of the material itself.…”
Section: Introductionmentioning
confidence: 99%